2011
DOI: 10.17221/1566-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent airway obstruction in horses - an allergic inflammation: a review

Abstract: Recurrent airway obstruction (RAO), also known as heaves, is a debilitating and incurable disease of the equine airway. Affected horses develop bronchoconstriction and neutrophilic airway inflammation as a result of exposure to specific airborne irritants and allergens such as hay mould and barn dust. Clinical signs of RAO include exercise intolerance, coughing, nostril flare and abdominal push related to respiratory effort. Evidence suggests that both the innate and acquired immune response contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 116 publications
0
19
0
Order By: Relevance
“…An excessive pro-allergic Th2 immune response cannot be documented in all cases of equine asthma [33], probably due to individual factors such as exacerbation phase, duration of the disease, genetic, and exogenous trigger factors and allergen load [34]. The initial concentration of IL-4 in the horses varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…An excessive pro-allergic Th2 immune response cannot be documented in all cases of equine asthma [33], probably due to individual factors such as exacerbation phase, duration of the disease, genetic, and exogenous trigger factors and allergen load [34]. The initial concentration of IL-4 in the horses varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the type of response in RAO have found conflicting results. The time point of sampling and the duration of stimulation, respectively, may influence results [ 9 ]. In the present study, we observed downregulation of both Th1 type ( IFNG ) and Th2-type cytokines ( IL4 , IL13 ) in RAO cells stimulated with HDE.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from humans, allergic asthmatic conditions occur naturally only in cats and horses [ 8 ]. The asthma-like disease in horses is called recurrent airway obstruction (RAO), which is a debilitating and incurable respiratory disease affecting stabled mature horses worldwide [ 9 11 ]. RAO-affected horses develop marked airway obstruction due to bronchospasm, inflammation, mucus accumulation and remodelling resulting in severe clinical signs such as coughing, respiratory distress and increased breathing effort during periods of exacerbation, which are triggered by hypersensitivity reactions to allergens and irritants mainly from hay dust [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,8 Clinical variables include cholinergic bronchospasm, hypercrinia and dyscrinia, nasal discharge, coughing, airway neutrophilia, airway remodeling, and edema, resulting in poor performance. 1,8,9 Cytosine-phosphate-guanosine-oligodeoxynucleotide (CpG-ODN) has been identified as a molecule that directs the immune system toward a cell-mediated Th1 pathway, away from the pro-allergic humoral Th2 line response, described as a Th2/Th1-shift. 3,10,11 Unmethylated CpG-ODN molecules exist naturally in prokaryotic viral and bacterial DNA and stimulate the mammalian immune system, via the Th1 pathway, against infectious agents.…”
mentioning
confidence: 99%